Diagnosis and organizational intervention. Methods used by organizations for their integral development - Tortolero, Rosalío; Gómez, José; Figueroa, Geovani; Moreno, Hector (Gestionar: revista de empresa y gobierno, 2024)
Organizational diagnosis is a tool used by organizations to detect areas of opportunity and implement strategic action plans through an intervention, enabling comprehensive development of the company. This research aims to identify the main methodologies and models of organizational diagnosis and intervention that can be used by organizations. A bibliographic review was conducted in databases such as Scopus, Elsevier, Redalyc, Dialnet, Scielo, and Google Scholar. Search descriptors included theoretical foundations of organizational diagnosis, organizational intervention, and the most commonly used diagnosis and methodology models by organizations. The records were limited to the period from 2008 to 2022, yielding 50 documents, of which 30 were selected for analysis, including scientific articles, books, and theses that presented a clear methodology for organizational diagnosis and intervention. The results show that organizational diagnosis involves two units of analysis; organizational and human behavior. For organizational intervention, three models were identified: related to structural changes, human behavior, and alterations that arise between structure and human behavior. It is concluded that organizational diagnosis and intervention are valuable methods for organizations aiming for growth and competitiveness. However, they are complex processes that are approached from various perspectives, which must be analyzed in depth.